The Armenian Text of Philo’s De Abrahamo 1‑16 - Nikolsky, Boris (Mesrop Mashtots Institute of Ancient Manuscripts)
This article discusses textual problems of the Armenian translation of Philo’s De Abrahamo (§1–6). The prevailing opinion that ms. V1040 is the codex optimus is questioned. A preliminary study of errors in the Armenian manuscript tradition allows to determine the place of V1040 among other witnesses and show that the correct Armenian text can be reconstructed only through a careful examination of all manuscript readings. The studied material also confirms Hans Lewy’s view that all known manuscripts of the Armenian translation of De Abrahamo go back to one archetype, which had already suffered considerable textual corruption.
Keywords: Philology